Zirconium oxide nano-ink for 3D printing and application of zirconium oxide nano-ink in printing dental materials

By performing surface esterification modification on zirconia nanopowders, the problem of insufficient dispersion of zirconia-based dental materials during 3D printing is solved, and a high dispersion and stability of zirconia nanoink is achieved, ensuring the uniform layer structure and stable printing effect of 3D printed dental materials.

CN119792098APending Publication Date: 2025-04-11ZHEJIANG ASIA GENERAL SOLDERING & BRAZING MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411964050.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During the 3D printing process, existing zirconia-based dental materials have poor spraying, nozzle blockage and uneven layer structure due to insufficient dispersion of zirconia nanopowders.

Method used

The surface modification of zirconia nanopowders is surface modified by surface esterification modification to enhance their interaction with the solvent, thereby obtaining high dispersion and stability of zirconia nanoinks.

Benefits of technology

The uniform dispersion of zirconia nanopowder in the solvent is achieved, which avoids spraying and nozzle blockage, and ensures the uniformity of layer structure and the stability of printing effect of 3D printed dental materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119792098A_ABST
    Figure CN119792098A_ABST
Patent Text Reader

Abstract

The invention provides zirconium oxide nano-ink for 3D printing and application of the zirconium oxide nano-ink in printing of dental materials, and the zirconium oxide nano-ink comprises the following raw materials in percentage by mass: 35-50% of surface esterification-like modified zirconium oxide nano-powder, 50-65% of a solvent and 0.5-2% of a surfactant. According to the zirconia nano-ink for 3D printing and the application of the zirconia nano-ink to printing of dental materials, the zirconia nano-powder is subjected to surface modification by utilizing a surface esterification-like modification means, and the interaction between the zirconia nano-powder and a solvent is enhanced, so that the zirconia nano-ink with high dispersity and stability is obtained; and the effect of the material in 3D printing of dental materials is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of dental ceramic materials, and in particular to a zirconium oxide nano-ink for 3D printing and an application thereof in printing dental materials. Background Art

[0002] With the growing demand for a better life, a large number of personalized high-end manufacturing industries have emerged. The use of 3D printing technology to manufacture zirconia-based dental materials is a typical example. Zirconia-based dental materials include crowns and bridges, inlays, porcelain veneers, abutments, implant systems, labial brackets, lingual brackets, etc. Traditionally, such materials are usually processed by subtractive manufacturing, but there is a lot of material waste, high energy consumption, and long production time. With the development and maturity of 3D printing technology, additive manufacturing of zirconia-based dental materials has gradually attracted attention. With the goal of localizing ceramic nano-inks with high technical barriers, the development of zirconia nano-inks with high dispersibility and stability is the key to achieving high-precision, high-repeatability, and high-quality-price ratio 3D printing of zirconia-based dental materials.

[0003] Ceramic nano ink is mainly composed of ceramic nano powder, solvent and additives, while zirconia nano ink is a stable colloidal suspension formed by zirconia nano particles dispersed in a liquid medium. After the printed ink is heat treated, the solvent evaporates, the nano particles collide, and a thick zirconia stacking structure is formed. There is almost no chemical reaction in this process. Therefore, when the nano particles are not dispersed sufficiently, it will cause the particles to aggregate and precipitate, resulting in poor jetting, nozzle clogging and uneven layer structure. Summary of the invention

[0004] Based on the technical problems existing in the background technology, the present invention proposes a zirconium oxide nano-ink for 3D printing and its application in printing dental materials. The surface of zirconium oxide nano-powder is modified by surface esterification modification, and the interaction between zirconium oxide nano-powder and solvent is enhanced, thereby obtaining a zirconium oxide nano-ink with high dispersibility and stability, ensuring its effect in 3D printing dental materials.

[0005] The invention provides a zirconium oxide nano-ink for 3D printing, wherein the raw materials thereof include, by mass percentage, 35-50% of surface ester-modified zirconium oxide nano-powder, 50-65% of solvent and 0.5-2% of surfactant.

[0006] In zirconia nano ink, since the zirconia nano powder is not evenly dispersed directly in the solvent, it is easy to cause the zirconia nano powder in the slurry to agglomerate into particles of a certain diameter, which is easy to block the nozzle during printing; the traditional modification effect of the dispersion uniformity and stability of the zirconia nano ink by adding a dispersant is limited. The present invention modifies the zirconia nano powder by surface esterification. Due to the surface grafting of organic groups, not only can the electrostatic and steric effects between particles be greatly increased, but also the uniformity of its dispersion in the solvent is ensured, giving the zirconia nano ink a relatively long stable storage capacity.

[0007] Preferably, the surface esterified zirconium oxide nanopowder is obtained by activating the zirconium oxide nanopowder with an inorganic strong acid and then subjecting the zirconium oxide nanopowder to a surface esterification reaction with an organic carboxylic acid.

[0008] The present invention firstly performs surface pretreatment on zirconium oxide nanopowder by using inorganic strong acid to activate the surface of zirconium oxide nanopowder and make the surface hydroxylated, and then performs surface esterification reaction by using organic carboxylic acid (between zirconium oxide and organic carboxylic acid, the surface of zirconium oxide provides empty electron orbits and the carboxylic acid group provides lone electron pairs, thus forming a coordination structure and even causing esterification reaction), thereby obtaining surface esterified zirconium oxide nanopowder, which not only has better dispersion stability than zirconium oxide nanopowder without any modification, but also has better dispersion stability than zirconium oxide nanopowder which is surface-modified by using organic carboxylic acid without inorganic strong acid pretreatment.

[0009] Preferably, the particle size of the zirconium oxide nanopowder is 0.05-0.5 μm.

[0010] Preferably, the inorganic strong acid is at least one of nitric acid, sulfuric acid, hydrochloric acid or perchloric acid, preferably nitric acid;

[0011] Preferably, the activation is specifically to add the zirconium oxide nanopowder into an inorganic strong acid solution with a pH of 0.5-1.5 and stir the solution for reaction.

[0012] Preferably, the organic carboxylic acid is at least one of oxalic acid, adipic acid, citric acid, malic acid, caprylic acid or lauric acid, preferably oxalic acid;

[0013] Preferably, the surface esterification reaction is specifically to add the zirconium oxide nanopowder activated by inorganic strong acid into an organic carboxylic acid solution with a concentration of 0.01-1 mol / L and stir for reaction.

[0014] Preferably, the solvent is at least one of an alcohol, ketone, ester or ether organic solvent;

[0015] Preferably, the alcohol organic solvent is at least one of ethanol, ethylene glycol, diethylene glycol or liquid polyethylene glycol, the ketone organic solvent is at least one of methyl isobutyl ketone, methyl isoamyl ketone, diisobutyl ketone or isophorone, the ester organic solvent is at least one of n-butyl acetate, 3-methoxybutyl acetate or dodecyl alcohol ester, and the ether organic solvent is at least one of diethylene glycol butyl ether, dipropylene glycol butyl ether or tripropylene glycol methyl ether.

[0016] Preferably, the surfactant is an anionic surfactant and / or a nonionic surfactant;

[0017] Preferably, the anionic surfactant is at least one of fatty alcohol sulfate, fatty alcohol polyoxyethylene ether sulfonate or fatty alcohol polyoxyethylene ether carboxylate, and the nonionic surfactant is at least one of fatty alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene ether carboxylate or alkyl glucoside.

[0018] The anionic surfactant and / or nonionic surfactant of the present invention can be adsorbed on the surface of the esterified zirconium oxide nanopowder to form a double electric layer. The double electric layers carry the same charge to generate repulsion to prevent the particles from approaching, further ensuring that the zirconium oxide nanopowder is evenly dispersed in the solvent and preventing its agglomeration and precipitation.

[0019] Preferably, the zirconium oxide nano ink raw material further comprises 0.1-1% of a dispersant by mass percentage;

[0020] Preferably, the dispersant is at least one of BYKJET-9151, DISPERBYK-111, DISPERBYK-2155, Solsperse 45000, Solsperse 41000 or Solsperse 84500.

[0021] Preferably, the zirconium oxide nano-ink raw material further comprises 0.1-2% of a resin binder by mass percentage;

[0022] Preferably, the resin binder is at least one of ethyl cellulose, cellulose acetate butyrate, polyvinyl butyral, vinyl chloride-vinyl acetate copolymer or methyl methacrylate-ethyl methacrylate copolymer.

[0023] The dispersant and binder of the present invention can further improve the viscosity and fluidity of the zirconium oxide nanopowder, and ensure that the zirconium oxide nano-ink can be smoothly ejected from the nozzle without obstruction and flocculation during 3D printing.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] Since the surface of zirconium oxide powder is Lewis acidic, it can accept ligand molecules that can provide lone pairs of electrons to form a relatively stable coordination structure. Therefore, if a "zirconium oxide-ligand molecule" complex can be formed, it can be further solvated in a solvent to form a multilayer structure of "zirconium oxide-ligand molecule-solvent". The electrostatic interaction and steric effect can increase the dispersion of the powder in the solvent and improve stability.

[0026] Based on this, the present invention selects an organic carboxylic acid with a strong lone pair electron providing ability as a surface modifier, and first uses an inorganic strong acid to perform surface pretreatment on the zirconium oxide nanopowder to activate the surface of the zirconium oxide nanopowder and make its surface hydroxylated, and then uses an organic carboxylic acid to perform a surface esterification or coordination reaction to obtain a surface esterified zirconium oxide nanopowder. In this way, the powder surface is modified by chemical means, and the dispersion effect of the powder in the solvent is improved. This is an application innovation related to surface and interface chemistry. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic diagram of the preparation process of zirconium oxide nano-ink for 3D printing of the present invention;

[0028] Figure 2 These are photos of the zirconium oxide nano-inks described in Comparative Examples 1 and 2 after being left to stand;

[0029] Figure 3 These are photos of the zirconium oxide nano-inks described in Example 1 and Comparative Examples 2-6 after being left to stand;

[0030] Figure 4 These are photos of the zirconium oxide nano-inks described in Example 1 and Comparative Examples 7-8 after being left to stand;

[0031] Figure 5 The SEM images of the zirconium oxide nano-inks after drying in Example 1 and Comparative Example 8 are shown in FIG. DETAILED DESCRIPTION

[0032] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.

[0033] Example 1

[0034] Reference Figure 1 , a zirconium oxide nano-ink for 3D printing, comprising raw materials by mass percentage: 45% of surface esterified zirconium oxide nano-powder, 52.5% of solvent (butyl diethylene glycol), 1% of anionic surfactant (sodium fatty alcohol polyoxyethylene ether sulfonate), 0.5% of dispersant (BYKJET-9151), and 1% of resin binder (polyvinyl butyral);

[0035] The above-mentioned surface ester-modified zirconium oxide nanopowder is prepared by the following preparation method:

[0036] The zirconium oxide nanopowder (D 50 The method comprises the following steps: adding a 0.1 μm particle size to a nitric acid aqueous solution at a pH of 1, stirring and reacting at room temperature for 24 hours, and centrifuging at a speed of 8500 rpm to obtain a surface-activated zirconium oxide nanopowder; dispersing the surface-activated zirconium oxide nanopowder in water, adding a 0.3 mol / L aqueous solution prepared with oxalic acid, wherein the molar ratio of the zirconium oxide nanopowder to the oxalic acid is 5:1, stirring and reacting at 70° C. for 24 hours, and centrifuging at a speed of 8500 rpm to obtain a surface-carboxylated zirconium oxide nanopowder; dispersing the surface-carboxylated zirconium oxide nanopowder in water, and centrifuging at a speed of 8500 rpm to complete a water washing, repeating the water washing twice, and then washing with alcohol (diethylene glycol butyl ether) twice in the above-mentioned manner to remove the oxalic acid and water on the surface of the zirconium oxide nanopowder that are not stably combined with the powder, so as to obtain the surface-esterified zirconium oxide nanopowder.

[0037] Reference Figure 1 , a method for preparing zirconium oxide nano-ink for 3D printing, comprising:

[0038] The surface ester-modified zirconium oxide nanopowder is added to the solvent, stirred and mixed evenly, and then anionic surfactant, dispersant and resin binder are added. After stirring and mixing evenly, the obtained mixed solution is poured into a ball mill lined with zirconium oxide, and zirconium oxide grinding balls with a diameter of 1 mm are added to the ball mill. The mass of the grinding balls is 3 times the mass of zirconium oxide. The ball mill is placed on a ball mill and ball milled at a rate of 200 r / min for 24 hours to obtain the zirconium oxide nano-ink for 3D printing. The obtained nano-ink is filtered through a 3μm organic nylon filter membrane needle filter with a diameter of 13 mm, and the filterable volume is greater than 10 mL.

[0039] Example 2

[0040] A zirconium oxide nano-ink for 3D printing, the raw material formula of which is the same as that of Example 1, except that the surface ester-modified zirconium oxide nano-powder is prepared by the following preparation method:

[0041] The zirconium oxide nanopowder (D 50The method comprises the following steps: adding a 0.1 μm particle size to a nitric acid aqueous solution at a pH of 1, stirring and reacting at room temperature for 24 hours, and centrifuging at a speed of 8500 rpm to obtain a surface-activated zirconium oxide nanopowder; dispersing the surface-activated zirconium oxide nanopowder in water, adding a 0.3 mol / L aqueous solution of adipic acid, wherein the molar ratio of the zirconium oxide nanopowder to the adipic acid is 5:1, stirring and reacting at 70° C. for 24 hours, and centrifuging at a speed of 8500 rpm to obtain a surface-carboxylated zirconium oxide nanopowder; dispersing the surface-carboxylated zirconium oxide nanopowder in water, and centrifuging at a speed of 8500 rpm to complete a water washing, repeating the water washing twice, and then washing with alcohol (diethylene glycol butyl ether) twice in the above-mentioned manner to remove the adipic acid and water on the surface of the zirconium oxide nanopowder that are not stably combined with the powder, so as to obtain the surface-esterified zirconium oxide nanopowder.

[0042] A method for preparing zirconium oxide nano-ink for 3D printing, the specific operation of which is referred to Example 1.

[0043] Example 3

[0044] A zirconium oxide nano-ink for 3D printing, the raw material formula of which is the same as that of Example 1, except that the surface ester-modified zirconium oxide nano-powder is prepared by the following preparation method:

[0045] The zirconium oxide nanopowder (D 50 The surface activated zirconium oxide nanopowder is dispersed in alcohol water (ethanol / water volume ratio is 4:1), 0.3 mol / L alcohol water solution (ethanol / water volume ratio is 4:1) prepared by lauric acid is added, the molar ratio of zirconium oxide nanopowder to lauric acid is 5:1, the surface carboxylation zirconium oxide nanopowder is obtained after stirring and reacting at 70°C for 24 hours, and then centrifuged at 8500 rpm to obtain surface carboxylation zirconium oxide nanopowder; the surface carboxylation zirconium oxide nanopowder is dispersed in water, and then centrifuged at 8500 rpm to complete a water washing, repeat the water washing twice, and then use the above method to wash with alcohol (diethylene glycol butyl ether) twice to remove the lauric acid and water on the surface of the zirconium oxide nanopowder that are not stably combined with the powder, so as to obtain the surface ester-modified zirconium oxide nanopowder.

[0046] A method for preparing zirconium oxide nano-ink for 3D printing, the specific operation of which is referred to Example 1.

[0047] Example 4

[0048] A zirconium oxide nano-ink for 3D printing, the raw material formula of which is the same as that of Example 1, except that the surface ester-modified zirconium oxide nano-powder is prepared by the following preparation method:

[0049] The zirconium oxide nanopowder (D 50 The method comprises the following steps: adding a zirconia nanopowder having a particle size of 0.1 μm) to a nitric acid aqueous solution having a pH of 1, stirring and reacting at room temperature for 24 hours, and centrifuging at a speed of 8500 rpm to obtain a surface-activated zirconium oxide nanopowder; dispersing the surface-activated zirconium oxide nanopowder in alcohol water (ethanol / water volume ratio of 4:1), adding a 0.3 mol / L alcohol aqueous solution prepared with octanoic acid (ethanol / water volume ratio of 4:1), wherein the molar ratio of the zirconium oxide nanopowder to octanoic acid is 5:1, stirring and reacting at 70°C for 24 hours, and centrifuging at a speed of 8500 rpm to obtain a surface-carboxylated zirconium oxide nanopowder; dispersing the surface-carboxylated zirconium oxide nanopowder in water, and centrifuging at a speed of 8500 rpm, washing with water once, repeating the water washing twice, and then washing with alcohol (diethylene glycol butyl ether) twice in the above manner to remove the octanoic acid and water on the surface of the zirconium oxide nanopowder that are not stably combined with the powder, thereby obtaining the surface-esterified zirconium oxide nanopowder.

[0050] A method for preparing zirconium oxide nano-ink for 3D printing, the specific operation of which is referred to Example 1.

[0051] Example 5

[0052] A zirconium oxide nano-ink for 3D printing, the raw material formula of which is the same as that of Example 1, except that the surface ester-modified zirconium oxide nano-powder is prepared by the following preparation method:

[0053] The zirconium oxide nanopowder (D 50 The method comprises the following steps: adding a zirconia nanopowder having a particle size of 0.1 μm) to a nitric acid aqueous solution having a pH of 1, stirring and reacting at room temperature for 24 hours, and centrifuging at a speed of 8500 rpm to obtain a surface-activated zirconium oxide nanopowder; dispersing the surface-activated zirconium oxide nanopowder in water, adding a 0.3 mol / L aqueous solution of malic acid, wherein the molar ratio of the zirconium oxide nanopowder to the malic acid is 5:1, stirring and reacting at 70° C. for 24 hours, and centrifuging at a speed of 8500 rpm to obtain a surface-carboxylated zirconium oxide nanopowder; dispersing the surface-carboxylated zirconium oxide nanopowder in water, and centrifuging at a speed of 8500 rpm, washing the surface-carboxylated zirconium oxide nanopowder once, repeating the water washing twice, and then washing with alcohol (diethylene glycol butyl ether) twice in the above manner to remove the malic acid and water on the surface of the zirconium oxide nanopowder that are not stably combined with the powder, thereby obtaining the surface-esterified zirconium oxide nanopowder.

[0054] A method for preparing zirconium oxide nano-ink for 3D printing, the specific operation of which is referred to Example 1.

[0055] Comparative Example 1

[0056] A zirconia nano-ink for 3D printing, the raw material formula of which is as described in Example 1, except that the zirconia nano-powder (D 50 The particle size is 0.1 μm) instead of the surface esterified zirconium oxide nanopowder.

[0057] A method for preparing zirconium oxide nano-ink for 3D printing, the specific operation of which is referred to Example 1.

[0058] Comparative Example 2

[0059] A zirconium oxide nano-ink for 3D printing, the raw material formula of which is the same as that of Example 1, except that the surface ester-modified zirconium oxide nano-powder is prepared by the following preparation method:

[0060] The zirconium oxide nanopowder (D 50 The invention discloses a method for preparing a surface-carboxylated zirconium oxide nanopowder having a particle size of 0.1 μm and dispersing the surface-carboxylated zirconium oxide nanopowder in water, adding a 0.3 mol / L aqueous solution prepared by oxalic acid, wherein the molar ratio of the zirconium oxide nanopowder to the oxalic acid is 5:1, and reacting the zirconium oxide nanopowder at 70°C for 24 hours by stirring, and then centrifuging the zirconium oxide nanopowder at a speed of 8500 rpm to obtain the surface-carboxylated zirconium oxide nanopowder; the surface-carboxylated zirconium oxide nanopowder is dispersed in water, and then centrifuged at a speed of 8500 rpm to obtain the surface-carboxylated zirconium oxide nanopowder. The ... washed with water once, and the water washing is repeated twice, and then the alcohol washing (diethylene glycol butyl ether) is performed twice in the above-mentioned manner to remove the oxalic acid and water on the surface of the zirconium oxide nanopowder that are not stably combined with the powder, so as to obtain the surface-esterified zirconium oxide nanopowder.

[0061] A method for preparing zirconium oxide nano-ink for 3D printing, the specific operation of which is referred to Example 1.

[0062] Comparative Example 3

[0063] A zirconium oxide nano-ink for 3D printing, the raw material formula of which is the same as that of Example 1, except that the surface ester-modified zirconium oxide nano-powder is prepared by the following preparation method:

[0064] The zirconium oxide nanopowder (D 50 The invention discloses a method for preparing a surface-carboxylated zirconium oxide nanopowder having a particle size of 0.1 μm) in water, adding a 0.3 mol / L aqueous solution of adipic acid, wherein the molar ratio of the zirconium oxide nanopowder to the adipic acid is 5:1, and reacting at 70°C with stirring for 24 hours, and then centrifuging at 8500 rpm to obtain surface-carboxylated zirconium oxide nanopowder; the surface-carboxylated zirconium oxide nanopowder is dispersed in water, and then centrifuged at 8500 rpm to obtain surface-carboxylated zirconium oxide nanopowder. The surface-carboxylated zirconium oxide nanopowder is dispersed in water, and then centrifuged at 8500 rpm to obtain surface-carboxylated zirconium oxide nanopowder, and then washed with water once, and then washed with water twice, and then washed with alcohol (diethylene glycol butyl ether) twice in the above-mentioned manner to remove the adipic acid and water on the surface of the zirconium oxide nanopowder that are not stably combined with the powder, so as to obtain the surface-esterified zirconium oxide nanopowder.

[0065] A method for preparing zirconium oxide nano-ink for 3D printing, the specific operation of which is referred to Example 1.

[0066] Comparative Example 4

[0067] A zirconium oxide nano-ink for 3D printing, the raw material formula of which is the same as that of Example 1, except that the surface ester-modified zirconium oxide nano-powder is prepared by the following preparation method:

[0068] The zirconium oxide nanopowder (D 50 The invention discloses a method for preparing a surface-carboxylated zirconium oxide nanopowder. The method comprises the following steps: dispersing a 0.3 mol / L alcohol aqueous solution (ethanol / water volume ratio of 4:1) prepared by lauric acid in an alcohol / water volume ratio of 4:1, and adding the 0.3 mol / L alcohol aqueous solution (ethanol / water volume ratio of 4:1) prepared by lauric acid, wherein the molar ratio of the zirconium oxide nanopowder to the lauric acid is 5:1, and reacting the mixture at 70°C for 24 hours by stirring, and then centrifuging the mixture at a speed of 8500 rpm to obtain a surface-carboxylated zirconium oxide nanopowder; dispersing the surface-carboxylated zirconium oxide nanopowder in water, and then centrifuging the mixture at a speed of 8500 rpm to complete a water washing, repeating the water washing twice, and then washing the mixture with alcohol (diethylene glycol butyl ether) twice in the above-mentioned manner to remove the lauric acid and water on the surface of the zirconium oxide nanopowder that are not stably combined with the powder, thereby obtaining the surface-esterified zirconium oxide nanopowder.

[0069] A method for preparing zirconium oxide nano-ink for 3D printing, the specific operation of which is referred to Example 1.

[0070] Comparative Example 5

[0071] A zirconium oxide nano-ink for 3D printing, the raw material formula of which is the same as that of Example 1, except that the surface ester-modified zirconium oxide nano-powder is prepared by the following preparation method:

[0072] The zirconium oxide nanopowder (D 50 The invention discloses a method for preparing a surface-carboxylated zirconium oxide nanopowder. The method comprises the following steps: dispersing a 0.1 μm nanopowder (with a particle size of 0.1 μm) in alcohol water (with an ethanol / water volume ratio of 4:1), adding a 0.3 mol / L alcohol aqueous solution (with an ethanol / water volume ratio of 4:1) prepared with octanoic acid, wherein the molar ratio of the zirconium oxide nanopowder to the octanoic acid is 5:1, stirring and reacting at 70°C for 24 hours, and centrifuging at a speed of 8500 rpm to obtain a surface-carboxylated zirconium oxide nanopowder; dispersing the surface-carboxylated zirconium oxide nanopowder in water, and centrifuging at a speed of 8500 rpm to complete a water washing, repeating the water washing twice, and then washing with alcohol (diethylene glycol butyl ether) twice in the above-mentioned manner to remove the octanoic acid and water on the surface of the zirconium oxide nanopowder that are not stably combined with the powder, thereby obtaining the surface-esterified zirconium oxide nanopowder.

[0073] A method for preparing zirconium oxide nano-ink for 3D printing, the specific operation of which is referred to Example 1.

[0074] Comparative Example 6

[0075] A zirconium oxide nano-ink for 3D printing, the raw material formula of which is the same as that of Example 1, except that the surface ester-modified zirconium oxide nano-powder is prepared by the following preparation method:

[0076] The zirconium oxide nanopowder (D 50 The invention discloses a method for preparing a surface carboxylated zirconium oxide nanopowder having a particle size of 0.1 μm and a particle size of 0.1 μm. The method comprises the following steps: dispersing the surface carboxylated zirconium oxide nanopowder in water, adding a 0.3 mol / L aqueous solution prepared with malic acid, wherein the molar ratio of the zirconium oxide nanopowder to the malic acid is 5:1, reacting the mixture at 70°C with stirring for 24 hours, and centrifuging the mixture at 8500 rpm to obtain surface carboxylated zirconium oxide nanopowder; dispersing the surface carboxylated zirconium oxide nanopowder in water, centrifuging the mixture at 8500 rpm, washing the mixture with water once, repeating the washing with water twice, and then washing the mixture with alcohol (butyl diglycol) twice in the above-mentioned manner to remove the malic acid and water on the surface of the zirconium oxide nanopowder that are not stably combined with the powder, thereby obtaining the surface ester-modified zirconium oxide nanopowder.

[0077] A method for preparing zirconium oxide nano-ink for 3D printing, the specific operation of which is referred to Example 1.

[0078] Comparative Example 7

[0079] A zirconium oxide nano-ink for 3D printing, the raw material formula of which is the same as that of Example 1, except that the surface ester-modified zirconium oxide nano-powder is prepared by the following preparation method:

[0080] The zirconium oxide nanopowder (D 50 The method comprises the following steps: adding a 0.1 μm particle size (with a particle size of 0.1 μm) into a sodium hydroxide aqueous solution with a pH of 13, stirring and reacting at room temperature for 24 hours, and centrifuging at a speed of 8500 rpm to obtain a surface-treated zirconium oxide nanopowder; dispersing the surface-treated zirconium oxide nanopowder in water, adding a 0.3 mol / L aqueous solution prepared with oxalic acid, wherein the molar ratio of the zirconium oxide nanopowder to the oxalic acid is 5:1, stirring and reacting at 70° C. for 24 hours, and centrifuging at a speed of 8500 rpm to obtain a surface-carboxylated zirconium oxide nanopowder; dispersing the surface-carboxylated zirconium oxide nanopowder in water, and centrifuging at a speed of 8500 rpm, washing with water once, repeating the washing with water twice, and then washing with alcohol (diethylene glycol butyl ether) twice in the above manner to remove the oxalic acid and water on the surface of the zirconium oxide nanopowder that are not stably combined with the powder, thereby obtaining the surface-esterified zirconium oxide nanopowder.

[0081] A method for preparing zirconium oxide nano-ink for 3D printing, the specific operation of which is referred to Example 1.

[0082] Comparative Example 8

[0083] A zirconium oxide nano-ink for 3D printing, the raw material formula of which is the same as that of Example 1, except that the surface ester-modified zirconium oxide nano-powder is prepared by the following preparation method:

[0084] The zirconium oxide nanopowder (D 50 The method comprises the following steps: adding a zirconia nanopowder having a particle size of 0.1 μm) to a nitric acid aqueous solution having a pH of 1, stirring and reacting at room temperature for 24 hours, and centrifuging at a speed of 8500 rpm to obtain a surface-activated zirconium oxide nanopowder; dispersing the surface-activated zirconium oxide nanopowder in diethylene glycol butyl ether, adding a 0.3 mol / L solution prepared with oxalic acid, wherein the molar ratio of the zirconium oxide nanopowder to the oxalic acid is 5:1, stirring and reacting at 70° C. for 24 hours, and centrifuging at a speed of 8500 rpm to obtain a surface-carboxylated zirconium oxide nanopowder; dispersing the surface-carboxylated zirconium oxide nanopowder in diethylene glycol butyl ether, and centrifuging at a speed of 8500 rpm, performing an alcohol washing, and repeating the alcohol washing three times to remove the oxalic acid and solvent on the surface of the zirconium oxide nanopowder that are not stably combined with the powder, so as to obtain the surface-esterified zirconium oxide nanopowder.

[0085] A method for preparing zirconium oxide nano-ink for 3D printing, the specific operation of which is referred to Example 1.

[0086] Figure 2 The following are photos of the zirconium oxide nano-inks described in Comparative Examples 1 and 2 after they were left to stand. Figure 2 It can be seen that the zirconium oxide nanopowder modified by oxalic acid surface esterification has significantly improved affinity with the solvent compared to the unmodified zirconium oxide nanopowder, which is helpful for powder dispersion, but the interaction between it and the solvent is weak and the dispersion effect is limited.

[0087] Figure 3 The following are photos of the zirconium oxide nano-inks described in Example 1 and Comparative Examples 2-6 after they were left to stand. Figure 3 It can be seen that for the zirconium oxide nanopowders modified by surface esterification of organic carboxylic acids alone, the modification ability of organic carboxylic acids decreases in the order of "oxalic acid > octanoic acid > malic acid > adipic acid ~ lauric acid" from the perspective of dispersion stability after standing for 72 hours. The modification ability of oxalic acid is much better than that of other carboxylic acids, which may be due to the strongest coordination ability of oxalic acid; also considering the pK a or pK a1 The pK values ​​of oxalic acid are 1.25 (25°C), malic acid 3.40 (25°C), adipic acid 4.41 (18°C), caprylic acid 4.89 (25°C), and lauric acid 5.3 (20°C). a The value is the lowest, and the relative acidity is much stronger than the other four carboxylic acids. The strong acid property may be the basis for oxalic acid to have better modification ability.

[0088] However, compared with the zirconium oxide nanopowder modified by simple oxalic acid surface esterification, before the oxalic acid surface modification, the surface is pretreated with inorganic strong acid (nitric acid) to activate the surface of the zirconium oxide powder and make its surface hydroxylated. The dispersion stability of the finally obtained zirconium oxide nano-ink is significantly better than that without nitric acid pretreatment.

[0089] Figure 4 The following are photos of the zirconium oxide nano-inks described in Example 1 and Comparative Examples 7-8 after they were left to stand. Figure 4 It can be seen that the zirconia nano-ink obtained by first activation and then modification under alkaline conditions is far inferior to the zirconia nano-ink obtained by first activation and then modification under acidic conditions; and the zirconia nano-ink obtained by first activation and then modification in an organic solvent under acidic conditions is also inferior to the zirconia nano-ink obtained by first activation and then modification in water under acidic conditions.

[0090] Figure 5 The SEM images of the zirconium oxide nano-inks after drying in Example 1 and Comparative Example 8 are shown in FIG. Figure 5 It can be seen that after the zirconium oxide nano-ink described in Example 1 is dried, the morphology of the zirconium oxide particles is approximately spherical or equiaxed, and the particle size is relatively uniform, which meets the requirements of 3D printing for particle morphology and size; the outlines between the particles are clearly visible, and there is no obvious agglomeration phenomenon, indicating that this nano-ink is well dispersed; while after the zirconium oxide nano-ink described in Comparative Example 8 is dried, the zirconium oxide particles are partially aggregated and connected together, and the dispersion effect is average.

[0091] Application Examples

[0092] A method for 3D printing dentures using the zirconium oxide nano-ink described in the above embodiment comprises:

[0093] Collect oral data and build a three-dimensional model of the denture; slice the model, convert it into STL format, and import it into the 3D printer manufacturing program; inject zirconium oxide nano-ink into the ink cartridge and 3D print the denture blank; dry, degrease and sinter the denture blank to obtain the denture.

[0094] Among them, preheating (130-200°C) is performed before sintering to remove the solvent, and then the dried embryo is sent to the sintering furnace for sintering. The sintering furnace is heated from 25°C to 250°C at a heating rate of 3°C / min, kept warm for 1 hour, and then heated from 250°C to 1500°C at a heating rate of 3°C / min, and kept warm for 1 hour.

[0095] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A zirconium oxide nano-ink for 3D printing, characterized in that: Calculated by mass percentage, the raw materials include: 35-50% of surface esterified zirconium oxide nano powder, 50-65% of solvent and 0.5-2% of surfactant.

2. The zirconium oxide nano-ink for 3D printing according to claim 1, characterized in that: The surface esterified zirconium oxide nanopowder is obtained by activating the zirconium oxide nanopowder with an inorganic strong acid and then subjecting the nanopowder to a surface esterification reaction with an organic carboxylic acid.

3. The zirconium oxide nano-ink for 3D printing according to claim 2, characterized in that: The particle size of the zirconium oxide nanopowder is 0.05-0.5 μm.

4. The zirconium oxide nano-ink for 3D printing according to claim 2 or 3, characterized in that: The inorganic strong acid is at least one of nitric acid, sulfuric acid, hydrochloric acid or perchloric acid, preferably nitric acid; Preferably, the activation is specifically to add the zirconium oxide nanopowder into an inorganic strong acid solution with a pH of 0.5-1.5 and stir the solution for reaction.

5. The zirconium oxide nano-ink for 3D printing according to any one of claims 2 to 4, characterized in that: The organic carboxylic acid is at least one of oxalic acid, adipic acid, citric acid, malic acid, caprylic acid or lauric acid, preferably oxalic acid; Preferably, the surface esterification reaction is specifically to add the zirconium oxide nanopowder activated by inorganic strong acid into an organic carboxylic acid solution with a concentration of 0.01-1 mol / L and stir for reaction.

6. The zirconium oxide nano-ink for 3D printing according to any one of claims 1 to 5, characterized in that: The solvent is at least one of an alcohol, ketone, ester or ether organic solvent; Preferably, the alcohol organic solvent is at least one of ethanol, ethylene glycol, diethylene glycol or liquid polyethylene glycol, the ketone organic solvent is at least one of methyl isobutyl ketone, methyl isoamyl ketone, diisobutyl ketone or isophorone, the ester organic solvent is at least one of n-butyl acetate, 3-methoxybutyl acetate or dodecyl alcohol ester, and the ether organic solvent is at least one of diethylene glycol butyl ether, dipropylene glycol butyl ether or tripropylene glycol methyl ether.

7. The zirconium oxide nano-ink for 3D printing according to any one of claims 1 to 6, characterized in that: The surfactant is an anionic surfactant and / or a nonionic surfactant; Preferably, the anionic surfactant is at least one of fatty alcohol sulfate, fatty alcohol polyoxyethylene ether sulfonate or fatty alcohol polyoxyethylene ether carboxylate, and the nonionic surfactant is at least one of fatty alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene ether carboxylate or alkyl glucoside.

8. The zirconium oxide nano-ink for 3D printing according to any one of claims 1 to 7, characterized in that: The raw materials also include 0.1-1% of dispersant by mass percentage; Preferably, the dispersant is at least one of BYKJET-9151, DISPERBYK-111, DISPERBYK-2155, Solsperse 45000, Solsperse 41000 or Solsperse 84500.

9. The zirconium oxide nano-ink for 3D printing according to any one of claims 1 to 8, characterized in that: The raw materials also include 0.1-2% of resin binder by mass percentage; Preferably, the resin binder is at least one of ethyl cellulose, cellulose acetate butyrate, polyvinyl butyral, vinyl chloride-vinyl acetate copolymer or methyl methacrylate-ethyl methacrylate copolymer.

10. Use of the zirconium oxide nano-ink according to any one of claims 1 to 9 in printing dental materials.